Analysis Of The Effect of Macronutrient Intake on Athletes' Fitness and Endurance (Case Study on Sports Teams in Indonesia) - Oddi Marmara Maryam; Farapti (JURNAL KESMAS DAN GIZI (JKG), 2025)
Macronutrient intake, including carbohydrates, protein and fat, plays an important role in supporting athlete performance and overall health. Previous research has shown that proper nutrition has the potential to improve athletes' endurance and fitness. However, mixed results raise questions about the real relationship between nutrient intake and athlete fitness. This study aimed to analyze the effect of macronutrient intake on athletes' fitness and endurance in Indonesian,  sports teams. This study applied an analytic descriptive design with a population of athletes from various sports in Indonesia. Data were obtained through literature study method. Data analysis was performed statistically to evaluate the relationship between variables. The study showed that there was no significant relationship between carbohydrate, protein, and fat intake and athletes' fitness level, with p values of 0.407 for carbohydrate, 0.523 for protein, and 0.208 for fat, respectively. These results suggest that although macronutrients are important, other factors also need to be considered. These findings emphasize the need to consider other factors, such as training patterns and psychological conditions, in an effort to improve athletes' fitness and performance, in addition to attention to macronutrient intake.